Kretek Capitalism: Making, Marketing, and Consuming Clove Cigarettes in Indonesia - Marina Welker (University of California Press, 2024)
Indonesia is the world's second-largest cigarette market: two out of three men smoke, and clove-laced tobacco cigarettes called kretek make up 95 percent of the market. Each year, more than 250,000 Indonesians die of tobacco-related diseases. To account for the staggering success of this lethal industry, Kretek Capitalism examines how kretek manufacturers have adopted global tobacco technologies and enlisted Indonesians to labor on their behalf in fields and factories, at retail outlets and social gatherings, and online. The book charts how Sampoerna, a Philip Morris subsidiary, uses contracts, competitions, and gender, age, and class hierarchies to extract labor from workers, influencers, artists, students, retailers, and consumers. Critically engaging nationalist claims about the commodity's cultural heritage and the jobs it supports, Marina Welker shows how global capitalism has transformed both kretek and the labor required to make and promote it. "Thoughtful and provocative, this is a superb book that will be widely read, especially by those who are looking for an antidote to current popular support of kretek."—Abidin Kusno, author of Jakarta: The City of a Thousand Dimensions "A magnificent book! Kretek Capitalism is destined to become a classic of both medical anthropology and public health scholarship."—Robert Proctor, author of Golden Holocaust: Origins of the Cigarette Catastrophe and the Case for Abolition
Keywords: 330; cigarette industry; Indonesia; spice; capitalism; tobacco